Attitudes of Turkish Parents Toward Sex Education of Their Intellectual Disability Children - Sarı, Hakan; Pürsün, Tuğba (Makara Journal of Health Research, 2022)
Background: Legal regulations in Turkey state that it is a fundamental right for children with intellectual disability to receive sex education. However, such education is highly limited due to the negative attitudes of these children’s parents. Therefore, the main aim of this study is to evaluate the attitudes of Turkish parents toward the sexual education of their intellectually disabled children. Methods: This quantitative study used the survey method on 311 parents who have children with intellectual disabilities. Data collection was carried out using a Likert-type scale questionnaire developed by the author. Socio-demographic variables were attained, and the data collected were analyzed. Results: Most of the parents (85%) believe that their children need support for sexual education, but cannot improve themselves to teach such subject without undergoing such education as well. However, the parents appear to have positive attitudes toward sexual education for their intellectually disabled children and believe that it can be provided adequately. Conclusions: Turkish parents have positive attitudes toward sex education for their children intellectual disability children. Therefore, adequate information about sex education might be needed from the professionals to empower the parents.